Antimicrobial and Volatile Compounds Study of Four Spices Commonly Used in Indonesian Culinary - Hamad, Alwani; Mahardika, M. Gigih Panji; Istifah, Istifah; Hartanti, Dwi (Journal of Food and Pharmaceutical Sciences, 2016)
The n-hexane extracts of the aerial parts of Ocimum x citriodorum and the leaves of Cymbopogon citratus, Syzygium aromaticum and Syzygium polyanthum were evaluated for their antimicrobial activity against some food borne microorganisms. Their volatile compounds were analyzed by gas chromatography/mass spectrometry (GC/MS). All extracts inhibited the growth of Bacillus subtilis. The extract of S. polyanthum showed the strongest inhibitory activity against Salmonella typhimurium. The growth of Staphylococcus aureus, Escherichia coli and Vibrio cholera were not inhibited by all extracts. The major volatile constituent of O. x citriodorum, C. citratus, S. aromaticum and S. polyanthum crude extracts were citral, germacrene D-14-ol, p-eugenol and squalene, respectively.